Understanding local governance: Institutinal forms of collaboration - Roiseland, Asbjorn (2011)
The article discusses institutional forms of governance, understanding governance as hybrid forms of collaboration, involving government, market actors and or civil society actors. By utilizing data from a study made of three Norwegian cities, six collaborative efforts are presented, and discussed in relatiion to analytical characteristics derived from both network theory and organizational theory. This analysis illustrates that these collaboration efforts can, on the one hand, be understood as something located between networks and organizations. On the other hand, one may argue they belong to none of the two theoretical catergories, implying the need for new theories regarding collaboration. These observati ons are followed by some theoretical reflections about how democraric governments can influence collaborations, and ensure that the common will can actually become real. - Reproduced.
Keywords: Local government